A dissipative self-sustained optomechanical resonator on a silicon chip - Huang, J. G. (2018)
In this letter, we report the experimental demonstration of a dissipative self-sustained optomechanical resonator on a silicon chip by introducing dissipative optomechanical coupling between a vertically offset bus waveguide and a racetrack optical cavity. Different from conventional blue-detuning limited self-oscillation, the dissipative optomechanical resonator exhibits self-oscillation in the resonance and red detuning regime. The anti-damping effects of dissipative optomechanical coupling are validated by both numerical simulation and experimental results. The demonstration of the dissipative self-sustained optomechanical resonator with an extended working range has potential applications in optomechanical oscillation for on-chip signal modulation and processing.